2014
DOI: 10.1371/journal.pone.0102789
|View full text |Cite
|
Sign up to set email alerts
|

Similar Associations of Tooth Microwear and Morphology Indicate Similar Diet across Marsupial and Placental Mammals

Abstract: Low-magnification microwear techniques have been used effectively to infer diets within many unrelated mammalian orders, but the extent to which patterns are comparable among such different groups, including long extinct mammal lineages, is unknown. Microwear patterns between ecologically equivalent placental and marsupial mammals are found to be statistically indistinguishable, indicating that microwear can be used to infer diet across the mammals. Microwear data were compared to body size and molar shearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…A prerequisite for using functional morphologies as ecological proxies, however, is the identification of ecomorphological traits that can be applied to higher level clades. Strong links between tooth morphology and diet have been previously established in mammals (Evans et al 2007;Boyer 2008;Christensen 2014;Pineda-Munoz et al 2017;Berthaume et al 2019), proving to be especially valuable for paleontological studies (Van Valkenburgh 1988;Janis 1995;Wilson et al 2012;Slater 2015;Grossnickle and Newham 2016;Chen et al 2019). The jaw correlates of diet presented in this study, especially JAPr distance and JAPr angle, may offer new functional traits that can be easily applied to broad studies of extant and fossil mammals.…”
Section: Macroevolutionary Studiesmentioning
confidence: 59%
See 3 more Smart Citations
“…A prerequisite for using functional morphologies as ecological proxies, however, is the identification of ecomorphological traits that can be applied to higher level clades. Strong links between tooth morphology and diet have been previously established in mammals (Evans et al 2007;Boyer 2008;Christensen 2014;Pineda-Munoz et al 2017;Berthaume et al 2019), proving to be especially valuable for paleontological studies (Van Valkenburgh 1988;Janis 1995;Wilson et al 2012;Slater 2015;Grossnickle and Newham 2016;Chen et al 2019). The jaw correlates of diet presented in this study, especially JAPr distance and JAPr angle, may offer new functional traits that can be easily applied to broad studies of extant and fossil mammals.…”
Section: Macroevolutionary Studiesmentioning
confidence: 59%
“…For instance, extensive studies of mammalian dentitions have shown strong associations between mammalian tooth shape and diet, including convergent morphological evolution in distantly related taxa that occupy similar ecological niches (Evans et al. ; Boyer ; Christensen ; Pineda‐Munoz et al. ; Berthaume et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is quantified by counting pits and scratches on the enamel of the occlusal surface of the teeth and has been widely used to study the diet of a variety of mammals6970. These features reflect the material properties of the food and exogenous items eaten71.…”
Section: Methodsmentioning
confidence: 99%